PROSPECTS FOR THE REALIZATION OF THE CONCEPT OF INFORMATION SOCIETY: OUTLINES FOR IMPROVING STATE POLICY - Dymytriiev, Volodymyr (Global Prosperity, 2024)
The article uses theoretical analysis to determine the prospects for implementing the concept of information society in the context of improving public policy. It is proved that the era of the information society, taking into account one of its key criteria, is coming to an end due to the reduction of employment in this sector. It is determined that in the current conditions of further development of the information society, the predominant employment should be dispersed relatively evenly between sectors or concentrated in some new sector. There are also qualitative changes with knowledge and information itself, which are the basis of the information society. Knowledge and information are beginning to transform into antipodes to some extent. There are certain dissonances. Many people feel a lack of awareness and difficulties in obtaining quality knowledge, despite the proliferation of information technology, and they have not become more informed or expanded their opportunities for obtaining it. Discussions are ongoing, ranging from whether the information society is being formed in accordance with the declared goals and to what extent these goals are being realized. On the other side of this spectrum, there is a discussion about the concept of the post-information society, as well as the unity of terminological approaches to the information and post-information society. It has been found that the vast majority of countries are involved in the formation of a model for adapting the information transformation of social development. Such changes at the global level lead to corresponding changes in the priorities of public policy in other countries to overcome the digital divide. It is shown that with such changes, technologically backward countries risk becoming victims of cybercolonialism by developed countries. This type of neo-colonialism may surpass the danger of raw material (traditional) colonialism that took place in the twentieth century.